Endoscopic Ultrasound‐Guided Creation of a Gastrogastric Conduit After Pancreaticoduodenectomy in a Patient with Prior Roux‐en‐Y Gastric Bypass. Issue 1 (2018) - Das, Rohit; Zeh, Herbert; Zureikat, Amer; Slivka, Adam; Papachristou, Georgios I.
ABSTRACT : N/A: We present a 65‐year‐old man with a history of a Roux‐en‐Y gastric bypass and an ampullary adenocarcinoma, treated initially with a Whipple operation, who developed chronic left upper quadrant pain as a consequence of retained gastric contents within a dilated gastric remnant that was no longer in continuity. This was treated successfully with the endoscopic ultrasound‐guided creation of a gastrogastric conduit via a covered metal stent. This represents a unique complication of pancreaticoduodenectomy in patients with a prior Roux‐en‐Y gastric bypass.